The behavioural characteristics of the model-80 model of the Irish economy - FitzGerald, John D.; Keegan, Owen (Statistical and Social Inquiry Society of Ireland, 1982)
For as long as governments have had the inclination or capability to influence economic events they have based their policies on their beliefs and prejudices as to how the economy works. These beliefs and prejudices constitute, de facto, a model of the economy. Similarly, while they may not admit it, businessmen have, for centuries, carried an incipient economic model around in their heads. Anyone who is interested in forecasting the future either with a view to altering the likely course of economic events, or accommodating their own activities to that likely course, has to form views on how the economy works. However, it is only really in the last thirty years that economists have begun to formalise these prejudices or views into a quantitative framework.
Read before the Society, 11 February 1982
Keywords: Model-80 model; Large scale macroeconomic models; Central Bank of Ireland; Irish economy; 314.15